2014
DOI: 10.1103/physrevlett.113.236403
|View full text |Cite
|
Sign up to set email alerts
|

Flatbands under Correlated Perturbations

Abstract: Flatband networks are characterized by the coexistence of dispersive and flatbands. Flatbands (FBs) are generated by compact localized eigenstates (CLSs) with local network symmetries, based on destructive interference. Correlated disorder and quasiperiodic potentials hybridize CLSs without additional renormalization, yet with surprising consequences: (i) states are expelled from the FB energy E_{FB}, (ii) the localization length of eigenstates vanishes as ξ∼1/ln(E-E_{FB}), (iii) the density of states diverges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
121
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 47 publications
3
121
0
1
Order By: Relevance
“…Seminal papers showed that interesting effects in condensed matter systems [14][15][16] are observed. Additionally, the influence of the singularity of flat band systems was investigated in the frame of the fractional quantum and magnon Hall effect [17,18] and energy localization in the presence of magnetic fields [19], spin-orbit coupling [20,21], or disorder [22,23]. Recently this topic attracted a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal papers showed that interesting effects in condensed matter systems [14][15][16] are observed. Additionally, the influence of the singularity of flat band systems was investigated in the frame of the fractional quantum and magnon Hall effect [17,18] and energy localization in the presence of magnetic fields [19], spin-orbit coupling [20,21], or disorder [22,23]. Recently this topic attracted a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…The fragile degeneracy guarantees the presence of a connected 1D structure that has an identical spectral response to that of a 3D disordered structure. Our results thus extend the field of correlated disorder [1,2,8,10,14,32] into network-like level statistics.Our approach utilizing the Hamiltonian transformation allows the finding of 1D isospectral structures from random networks deterministically, in contrast to numerical searching techniques, e.g. genetic algorithm.…”
mentioning
confidence: 89%
“…Due to the critical needs in light harvesting [6], robust bandgaps [7,8], and ultrafast optics [9], disordered optical materials have also been intensively studied to exploit their broadband responses. Although one-(1D) [8,10], two-(2D) [1,11,12], and three-dimensional (3D) [13] disordered structures have been considered promising candidates for broadband and omnidirectional operations, the deliberate control of disordered structures [1,3,7,8,14] has been achieved only in 1D or 2D structures, owing to the difficulty of manipulating 3D randomness.To understand the role of the 'dimension' in optics, we can employ the interdisciplinary viewpoint from network theory. For the structures composed of coupled resonances, light flows inside those can be interpreted as signal transport over graph networks [14][15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The CLS existence has been experimentally probed in the same settings where FB lattices may be realized, as mentioned above: waveguiding arrays [7][8][9], exciton-polariton condensates [10], and atomic BECs [4]. The impact of various perturbations, such as disorder [5,11], correlated potentials [12,13], and external magnetic and electric fields [14], on FB lattices and the corresponding CLSs was studied too.…”
Section: Introductionmentioning
confidence: 99%